2013
DOI: 10.1037/a0033630
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of quantity processing of numeral classifiers.

Abstract: Objective: Classifiers play an important role in describing the quantity information of objects. Few studies have been conducted to investigate the brain organization for quantity processing of classifiers. In the current study, we investigated whether activation of numeral classifiers was specific to the bilateral inferior parietal areas, which are believed to process numerical magnitude. Method: Using functional MRI, we explored the neural correlates of numeral classifiers, as compared with those of numbers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…"zhi" is the unit for animal) (Her, 2012;Li et al, 2008). A previous neuroimaging study indicated that the process of reading Chinese numeral classifiers does not involve the same brain response profiles as judging Arabic digits and dot quantities, suggesting that quantity processing of classifiers is independent of numerical processing (Cui et al, 2013). We take this as evidence that the Chinese classifiers do not elicit automatic and explicit quantity cues when reading Chinese nouns.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…"zhi" is the unit for animal) (Her, 2012;Li et al, 2008). A previous neuroimaging study indicated that the process of reading Chinese numeral classifiers does not involve the same brain response profiles as judging Arabic digits and dot quantities, suggesting that quantity processing of classifiers is independent of numerical processing (Cui et al, 2013). We take this as evidence that the Chinese classifiers do not elicit automatic and explicit quantity cues when reading Chinese nouns.…”
mentioning
confidence: 70%
“…This manipulation allowed us to match the reading and judgment components of the two problem types such that the only difference was the need to derive a mathematical model. A previous neuroimaging study indicated that the process of reading Chinese numeral classifiers does not involve the same brain response profiles as judging Arabic digits and dot quantities, suggesting that quantity processing of classifiers is independent of numerical processing (Cui et al, 2013). The Chinese mandarin system provides suitable materials for this manipulation, because of its lack of a counting syntax (Li, Barner, & Huang, 2008).…”
mentioning
confidence: 99%
“…The most relevant previous study is Cui et al [ 10 ], where a functional magnetic resonance imaging (fMRI) experiment compared the brain activities of processing classifiers with those of processing tool nouns, numbers, and dot arrays. Tool nouns are non-quantity words which refer to concrete objects used as tools, utensils, or instruments, e.g., liandao (sickle) and laba (trumpet).…”
Section: Introductionmentioning
confidence: 99%
“…One possible critical reason why Cui et al [ 10 ] did not find the IPS more activated for processing C/Ms than processing tool nouns is that their experimental materials of the so-called “classifiers” mixed up Cs and Ms and thus no distinction was made between Cs and Ms. Yet, as reviewed above, linguistic studies suggested that Cs differ significantly from Ms [e.g., 5 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation